Effects of COVID-19 Lockdown on Movement Disorders Patients With Deep Brain Stimulation: A Multicenter Survey - Piano, Carla; Bove, Francesco; Tufo, Tommaso; Imbimbo, Isabella; Genovese, Danilo; Stefani, Alessandro; Marano, Massimo; Peppe, Antonella; Brusa, Livia; Cerroni, Rocco; Motolese, Francesco; Di Stasio, Enrico; et al. (Frontiers in Neurology, 2020)
Background: The containment measures taken by Italian government authorities during the SARS-CoV-2 pandemic caused the interruption of neurological activities of outpatient clinics. Vulnerable patients, as Parkinson’s disease (PD) and dystonic patients with deep brain stimulation (DBS), may have an increased risk of chronic stress related to social restriction measures and may show a potential worsening of motor and psychiatric symptoms. Methods: This cross-sectional multicenter study was carried out during the SARS-CoV-2 pandemic and was based on a structured survey administered during a telephone call. The questionnaire was designed to gather motor and/or psychiatric effects of lockdown and COVID-19 epidemiologic information in PD and dystonic patients with a functioning DBS implant. Results: Were included in the study 104 patients, 90 affected by PD and 14 by dystonia. Forty-nine patients reported a subjective perception of worsening of global neurological symptoms (motor and/or psychiatric), related to the containment measures. In the multivariate analysis, having problems with DBS device was the only independent predictor of motor worsening (OR=3.10 [1.22-7.91], p=0.018). Independent predictors of psychiatric worsening were IADL score (OR=0.78 [0.64-0.95], p=0.012) and problems with DBS (OR=5.69 [1.95-16.62], p=0.001). Only one patient underwent nasopharyngeal swabs, both negatives, and no patient received diagnosis of COVID-19. Conclusions: Lockdown restriction measures were associated with subjective worsening of motor and psychiatric symptoms in PD and dystonic patients treated by DBS, and they may have exacerbated the burden of neurological disease and increased the chronic stress related to DBS management.